Soil compaction in crop-livestock-forest integration systems of five years of implantation and use - Souza, Jéssica Fernanda Dias; Bonini, Carolina dos Santos Batista; Mateus, Gustavo Pavan; Souza, Caroline Teodoro de; Perusso, Rafael Luís Sanchez; Pedro, Fabricio Gomes; Oliverio, Gabriela Lozano (Revista de Ciências Agroveterinárias, 2020)
The objective of this work was to analyze the physical attributes of a Oxisol of different crop-livestock-forest integration systems implanted in 2012 and in use since then. The experimental design was a randomized complete block design, with four replications and four treatments: ILP - crop - livestock integration; ILPF 1L - agrosilvopastoral system, with one eucalyptus line; ILPF 3L - agrosilvopastoral system, with three eucalyptus lines; and EUC - exclusive plantation of eucalyptus (forest). From June 2017 to May 2018, mechanical penetration and gravimetric soil moisture evaluations were carried out to monitor soil compaction in three depths of soil: 0-0.05; 0.05-0.10 and 0.10-0.20 m. The results of the research show that there was a significant difference in the soil attributes studied, being the highest compaction found in the treatment ILPF 3L (0.05-0.10 m) near the limit considered ideal for a good development of the plants. Gravimetric soil moisture did not influence compaction results. In general, the results show that in the soil conditions of the region considered fragile and highly susceptible to compaction, the presence of the animals does not cause a very drastic compaction to the soil, with values lower than the critical limit of 2 MPa.